2008
DOI: 10.1002/path.2327
|View full text |Cite
|
Sign up to set email alerts
|

POU5F1, encoding a key regulator of stem cell pluripotency, is fused to EWSR1 in hidradenoma of the skin and mucoepidermoid carcinoma of the salivary glands

Abstract: The EWSR1 gene is known to play a crucial role in the development of a number of different bone and soft tissue tumours, notably Ewing's sarcoma. POU5F1 is expressed during early development to maintain the totipotent status of embryonic stem and germ cells. In the present study, we report the fusion of EWSR1 and POU5F1 in two types of epithelial tumours: hidradenoma of the skin and mucoepidermoid carcinoma of the salivary glands. This finding not only broadens considerably the spectrum of neoplasms associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 40 publications
8
86
4
1
Order By: Relevance
“…7,12,[19][20][21] The remaining 10 fusion-negative, high-grade tumors were also negative for the EWSR1-POU5F1 fusion previously identified in high-grade mucoepidermoid carcinomas. 22 These findings support the notion that low-grade mucoepidermoid carcinomas are fusion-positive and genetically stable tumors with few genomic imbalances. The fact that CRTC1-MAML2 is a potent oncogene with effects on critical signaling pathways (Enlund et al, unpublished data) 17,29 might at least partly explain why these tumors contain relatively few copy number alterations.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…7,12,[19][20][21] The remaining 10 fusion-negative, high-grade tumors were also negative for the EWSR1-POU5F1 fusion previously identified in high-grade mucoepidermoid carcinomas. 22 These findings support the notion that low-grade mucoepidermoid carcinomas are fusion-positive and genetically stable tumors with few genomic imbalances. The fact that CRTC1-MAML2 is a potent oncogene with effects on critical signaling pathways (Enlund et al, unpublished data) 17,29 might at least partly explain why these tumors contain relatively few copy number alterations.…”
Section: Discussionsupporting
confidence: 76%
“…16,19 Fluorescence In Situ Hybridization (FISH) Analysis FISH analyses for detection of the CRTC1-MAML2 and EWSR1-POU5F1 gene fusions were performed on 3 mm formalin-fixed paraffin-embedded sections using dual-color break-apart rearrangement probes for the MAML2 (ZytoVision GmbH, Bremerhaven, Germany) and EWSR1 genes (Vysis, Downer's Grove, IL) as previously described. 22,28 To validate recurrent copy number alterations detected by arrayCGH we performed FISH analyses using locus-specific probes for MALT1 located at 18q21.32 (MALT1 Break-apart probe; Cytocell, Cambridge, UK) and MECOM located at 3q26.2 (MECOM/ RUNX1 t(3;21) Fusion-probe; Kreatech Diagnostics, Amsterdam, The Netherlands). Locus-specific probes for CCND1 (IGH/ CCND1 Translocation Probe; Cytocell) and HER2 (Vysis) were used to confirm amplifications involving 11q and 17q sequences.…”
Section: Rt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…10 Hidradenoma, a biphasic epithelial skin appendage tumor with occurrence of ductal/glandular and cystic structures, earlier thought to be a clear cell myoepithelioma, 13,14 possess in a subset of cases the specific fusion CRTC1-MAML2, which has been also described in mucoepidermoid carcinomas and Warthin's tumors of salivary glands. 15,16 One study demonstrated the occurrence of EWSR1-POUF5F1 fusion in hidradenomas, 17 whereas Antonescu et al 10 did not find an EWSR1 rearrangement in five eccrine hidradenomas. 10 Therefore, one could speculate whether these described lesions by Mö ller et al 17 are more related to myoepithelial tumors.…”
Section: Ewsr1 In Cutaneous Myoepitheliomamentioning
confidence: 99%
“…10 Therefore, one could speculate whether these described lesions by Mö ller et al 17 are more related to myoepithelial tumors. 17 The much more common occurring and investigated myoepithelial tumors of the salivary glands are known for a different genetic background, which contains rearrangements of PLAG1 and HMGA2. 18 A differential diagnosis of cutaneous myoepithelial tumors in our opinion represents epithelioid sarcoma, especially the very rarely occurring myxoid variant.…”
Section: Ewsr1 In Cutaneous Myoepitheliomamentioning
confidence: 99%